LOCAL WISDOM TOURISM DEVELOPMENT OF SEMARANG WITH TOURISM CLUSTER SYSTEM AS AN ACTION FOR SUSTAINABLE ECONOMICS DEVELOPMENT - Umi Thoifah Amalia; Endang Purwaningsih (Proceedings Education and Language International Conference, 2017)
Semarang is the capital of Central Java, Indonesia. Semarang is the city that can through the path pantura. The development of local tourism in Semarang is not accompanied with the welfare of its citizens. In fact, Semarang is the center of the city from the province of Central Java and through the path pantura, beside that Semarang also has many local culture, culinary tours and souvenirs typical of the local culture. Semarang has a lot of potention to develop, it means semarang needs some management that can support the semarang tourism for the welfare of society. The real is the optimalization of local wisdom in Semarang is not enough to develop a lot of potention of the city, the packaging of tourism that are still monotony. So, it only has low selling price. The right effort that can use to develop the local tourism in Semarang is implement a package tour with using the cluster. The tourism cluster system is a system that uses the potential and uniqueness of each region, especially the outcome of the local wisdom. Tourism cluster development will give added value of Semarang Tourism Development. Tourism cluster can be divided into a) cluster of arts and culture, b) cluster of religion tourism c) cluster of historical tourism, and d) cluster souvenirs local culture. The cluster of the tourism is used to make Economics Sustainability. This paper is using the approach of the sort of descriptive set of qualitative. This paper is using the primary and secondery data. Keywords: Local tourism, tourist cluster system, Semarang city